Climate Change Anxiety Related to Women’s Health Among Health Sciences Students - Şenol, Derya Kaya; Özkan, Semiha Aydın; Omuş, Durdu Cennet (UI Scholars Hub, 2025)
Background: Climate change impacts are unequally distributed globally, with children, women, pregnant women, the elderly, marginalized populations, and refugees bearing a disproportionate burden. This study aims to determine the levels of related anxiety among female students and to examine the relationship between the anxiety and their perceptions, knowledge levels, and health behaviors related to women’s health. Methods: The study has a descriptive cross-sectional design. The study population included women students enrolled in the fall semester of the 2023–2024 academic year at the Faculty of Health Sciences of a university between October and December 2023. Personal Information Form and Climate Change Anxiety Scale for Women's Health were used as data collection forms. Results: The results show that students need to have up-to-date information on climate change, they should be members of associations/organizations dealing with climate change, they should have awareness of the effects of climate change on the world and human life, the economic level of individuals, their physical/physiological and mental health, nutrition and health care needs and that climate change/climate crisis course should be included in the curriculum. Conclusions: Given the scale of the issue and the significant number of healthcare professionals, it is recommended to integrate into the curriculum of the departments that train personnel programs.